In Situ Monitoring of Dispersion Dynamics of Carbon Nanotubes during Sonication Using Electrical Conductivity Measurements. (15th October 2015) - Ali, Syed Sadiq; Shahabuddin, Mohammed; Asif, Mohammad
Abstract : The main challenge in the fabrication of carbon nanotube- (CNT-) based composite materials is the optimization of the sonication time in order to obtain homogenous and uniform dispersion of CNTs. Past studies mostly relied on postprocessing characterization techniques to address this issue. In the present, however, in situ monitoring of dispersion dynamics of CNTs in distilled water is carried out using instantaneous conductivity measurements. Using a computer controlled data acquisition system, the time evolution of the solution conductivity was carefully recorded. The data were then used to evaluate the intensity of turbulent fluctuations, which clearly highlighted the existence of three distinct sonication phases. During the first phase, the conductivity fluctuations initially increased attaining ultimately a maximum, thus indicating the occurrence of large agglomerates of CNTs. During the second phase of sonication, the solution conductivity showed a rather steep increase while fluctuations steadily declined. This phenomenon can be attributed to the breakdown of large CNT agglomerates, resulting in greater dispersion homogeneity of CNTs. During the third phase, after almost 650 kJ/L of sonication energy, the conductivity increase was almost negligible. The fluctuation intensity also remained constant during this phase signifying that the further sonication was no longer required.